Ecological and Evolutionary Consequences of Anticancer Adaptations - Justine Boutry; Antoine M. Dujon; Anne-Lise Gerard; Sophie Tissot; Nick Macdonald; Aaron Schultz; Peter A. Biro; Christa Beckmann; Rodrigo Hamede; David G. Hamilton; Mathieu Giraudeau; Beata Ujvari; et al. (iScience, 2020)
Summary: Cellular cheating leading to cancers exists in all branches of multicellular life, favoring the evolution of adaptations to avoid or suppress malignant progression, and/or to alleviate its fitness consequences. Ecologists have until recently largely neglected the importance of cancer cells for animal ecology, presumably because they did not consider either the potential ecological or evolutionary consequences of anticancer adaptations. Here, we review the diverse ways in which the evolution of anticancer adaptations has significantly constrained several aspects of the evolutionary ecology of multicellular organisms at the cell, individual, population, species, and ecosystem levels and suggest some avenues for future research.